Role of teacher in nurturing desired Outcome based teaching and performance based assessment - Meenakshi (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
It has been argued, and for good reasons, that outcome-based education (OBE) represents the most important development in education in the past two decades. A clear specification of the end product of training and the associated learning outcomes is essential for effective curriculum planning. It‘s like the same that we won‘t be approaching an architect to build a house until we had approved plans. The seeds we plant in our garden and how we cultivate them, including the growing conditions we create and the fertilizers we use, will depend on the plants we expect to grow. In the same way, in OBE recognition is given to the importance of the end product of the training programme and the competencies expected of the learners trained. Who could disagree with that? In this OBE backward or reverse-planning model, the course content and the teaching, learning and assessment methods are derived from the expected learning outcomes. This paper was written for practitioners in higher education, including academics and instructional designers who are engaged in curriculum revision. It aims to examine the notion of outcomes-based education, survey the literature and provide a critical review of the outcomes-based approach to quality assessment and curriculum improvement in higher education. The outcomes-based approach is completely student-centered, which focuses on what students know and can actually do. Sharpening the focus onto student learning outcomes goes beyond mere tinkering with traditional structures and methods; it really constitutes a paradigm shift in educational philosophy and practice